The equation of the line can be written as y-kx-b=0. The distance of the line from center of the circle (origin in this case) is given by mod(b/sqrt(1+k^2)). (Distance of a line ax+by+c from x1,y1 is given by ax1+by1+c/sqrt(a^2+b^2) ).

For this line to be a tangent to the given circle , distance from origin to the line must be one.

Solving the two equations , we get b+sqrt(1+k^2) = 1 ; i,e, b^2-k^2 = 1.

Statement 1 : Not sufficient.

Statement 2 : Not sufficient.

Both the statements together : We get bk=0. b^2-k^2=1 or -1. Hence Not sufficient

Hence the answer must be E.

_________________

" The few , the fearless "